ОЛАМНИНГ ЛИСОНИЙ МАНЗАРАСИДА ФРАЗЕОЛОГИЗМЛАР НАЗАРИЯСИ ТАВСИФИ - Бахронова, Д. (SCIENCE and SOCIETY, 2021)
Phraseology is a basic unit of the modern phraseological system, a complex, multifaceted linguistic phenomenon that differs from the general number of existing word combinations in the language. Dozens of criteria and signs have been noted and recommended by linguists as the object of study of phraseological units. The fact that the status of phraseology in the scientific literature is not sufficiently clear has caused a great deal of controversy among phraseologists and linguists.